2008
DOI: 10.55095/achot2008/078
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Humerus Fractures - Current Treatment Options

Abstract: Proximal humerus fractures represent an increasing challenge for the health system due to epidemiological changes. As estimated by a Finnish study group the number of fractures may triple by the year 2030. The majority of patients with these fractures are older than 60 years and in this population most of the proximal humerus fractures have been related to osteoporosis. Nondisplaced fractures and fractures with minimal displacement and adequate stability are usually successfully treated non-operatively. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
0
2
0
4
Order By: Relevance
“…[18,19] Gradl et al [18] reported that the most common complications after plate applications were malunion and fracture displacement, and the most common complication after IMN application was proximal screw perforation. Konrad et al [20] reported that malunion and non-union were the most common complications regardless of plate or IMN application. In similar studies, it has been reported in the literature that the non-union rate is independent of implant selection.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] Gradl et al [18] reported that the most common complications after plate applications were malunion and fracture displacement, and the most common complication after IMN application was proximal screw perforation. Konrad et al [20] reported that malunion and non-union were the most common complications regardless of plate or IMN application. In similar studies, it has been reported in the literature that the non-union rate is independent of implant selection.…”
Section: Discussionmentioning
confidence: 99%
“…Zlomeniny horního konce kosti pažní jsou po zlomeninách proximálního femuru a distálního radia třetí nejčastější zlomeninou, přesto jejich počet uváděný různými autory kolísá od 5 do 10 % (7,17). Jejich incidence s věkem exponenciálně stoupá, což spolu se stárnutím populace a vzestupem zastoupení seniorů v posledních letech představuje do budoucna jistou medicínskou a ekonomickou zátěž (2,6,8,10,17,18,19). Jednoznačný léčebný koncept zejména pro dislokované víceúlomkové (tří-a čtyř-) zlomeniny chybí (16,27,29,34).…”
Section: úVodunclassified
“…Větší počet operačních technik, z nichž ani jedna nemá výraznější preferenci, je důkazem stále chybějícího konsenzu v léčbě (11). Nepříliš dobré výsledky a vysoký počet komplikací u dříve užívaných dlah, hlavně v osteoporotickém terénu, vedl k rozvoji úhlově stabilních implantátů, které mají výhodnější biomechanické vlastnosti a zároveň splňují kritéria miniinvazivity (1,13,18,24,33). Valná většina prací popisuje výsledky pouze jedné techniky a neporovnává je navzájem.…”
Section: Sběr Datunclassified
See 1 more Smart Citation
“…LCP může být zásadní výhodou ve stabilitě osteosyntézy u kosti se sníženou minerální hustotou a tříštivou metafyzární zónou distálního humeru (12). Tyto vlastnosti LCP systému jsou prokázané i v jiných anatomických lokalitách (11,13,14,27,28). Perren ve svém referátu o kostním hojení popisuje lepší prokrvení oblasti zlomeniny při fixaci úhlově stabilními implantáty s lepším funkčním výsledkem a bezpečným hojením provázeným plnou obnovou funkce (20).…”
Section: Výsledkyunclassified